2015
DOI: 10.1039/c5cp04723d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ceria based superhydrophobic coating on Ni20Cr substrate via cathodic electrodeposition

Abstract: In this work, superhydrophobic cerium oxide coating surface (111) with dual scale texture on Ni20Cr substrate is obtained by combination of electropolishing the substrate and subsequent cathodic electrodeposition and long-term UVH surface relaxation. To form hierarchical structures of CeO2 is controllable by varying the substrate roughness, and electropolishing period. The results indicated that at the optimal condition, the surface of the cerium oxide coating showed a superhydrophobicity with a great water co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 42 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…REOs are of recent interest [21][22][23][24]. Most reports preparing hydrophobic REO coatings utilized dry processes such as sputtering [21] or atomic layer deposition [24].…”
Section: Introductionmentioning
confidence: 99%
“…REOs are of recent interest [21][22][23][24]. Most reports preparing hydrophobic REO coatings utilized dry processes such as sputtering [21] or atomic layer deposition [24].…”
Section: Introductionmentioning
confidence: 99%
“…This can be confirmed by comparing the roughness results displayed in Table 2. Figure 5b,d shows that the electrodeposition method creates a cauliflower-like structure due to the growth of cerium particles [28,29]. We found that the size of the nano-asperities formed on the AS samples were smaller than for the Al-Mg samples due to the greater number of preferential sites.…”
Section: Cathodic-electrodeposited Coatingsmentioning
confidence: 83%
“…In this work, we propose top-down and bottom-up strategies to produce superhydrophobic cerium-based coatings on Al-Mg alloy and AS substrates. Similar strategies have been used earlier for different substrates [8,28,29]. Unlike other works reported for the same materials and similar purposes, the protocols described here do not require etching with strong acids for the texturization [23].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The actual trends for hydrophobic and super-hydrophobic coating layers development are based on the formation of highly textured cerium oxide primers with micro and nanoflower [42], Gecko footprint [43] morphologies. This approach enables to avoid also the snow and ice heaping on the wings, which was the suspected reason for the aircraft crash at 7th of February 1958 in Munich, which was appeared to be a great disaster for the "Manchester United" football team during large years [44].…”
Section: Exterior Protective Coatings and Layers: Basic Requirementsmentioning
confidence: 99%